Analisis Faktor-faktor yang mempengaruhi Pertumbuhan Ekonomi dan pengaruhnya terhadap Kemiskinan di Kabuparten/Kota Provinsi Jambi - Irmanelly Irmanelly; Ardi Afrizal; Faradilla Herlin (J-MAS (Jurnal Manajemen dan Sains), 2021)
The first research objective is to analyze export and import factors in influencing economic growth in the District/ City of Jambi Province with partial and simultaneous test results that exports and imports affect economic growth by 12.9%, meaning that if exports and imports increase, economic growth will also increase. increased and evidenced by the significance value below alpha 5% or 1.8% and 1.5%. The second research objective is an analysis of economic growth and poverty that in general economic growth has not had a significant effect on poverty in the District/ City of Jambi Province, this can be seen from the calculation of the R-squared value of 1.3% with a significance level above 10% or alpha 61,42%.